1986
DOI: 10.1080/03015521.1986.10426126
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of black currant (Ribes nigrum) established from cuttings

Abstract: Hardwood cuttings of black currant (Ribes nigrum L.) were closely planted in rows during winter in two successive years. Vegetative shoots produced by cuttings during the first season and by fruiting plants during the second and third seasons were measured and counted. The final length of shoots was related to the time of shoot appearance, earlier shoots (with the exception of fruiting wood extension growth) being longer than those arising later in the season. Shoots originating from buds on cuttings carried 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Such early precocity of blackcurrants results from the formation of flower buds on 1-year-old shoots (Rhodes, 1986). The fertiliser treatment groups showed higher fruit yields than that of the control group (Table 6).…”
Section: Yield and Fruit Qualitymentioning
confidence: 96%
“…Such early precocity of blackcurrants results from the formation of flower buds on 1-year-old shoots (Rhodes, 1986). The fertiliser treatment groups showed higher fruit yields than that of the control group (Table 6).…”
Section: Yield and Fruit Qualitymentioning
confidence: 96%
“…treatment has consistently yielded highest. The slight reduction during the 1984/85 season can be explained by an observation made in a trial conducted by Rhodes (1986). Rhodes stated that with increasing age, fruit bearing gradually becomes restricted to extension growth.…”
Section: Irrigation Effectsmentioning
confidence: 99%
“…Management options Rhodes (1986) found a positive correlation between cane length and yield per plant at the frrst harvest, 325 followed by a tendency towards higher yields at the second and third harvests. He suggested that increased production during the frrst few years of cropping might be possible through management practices which would increase the number and length of shoots at the frrst harvest.…”
Section: Irrigation Effectsmentioning
confidence: 99%